Ukryte formy zachowań agresywnych u dziewcząt - Krajnčan, Mitja; Pavel, Jana Rapuš (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
Nowadays, increasingly more attention is being paid to the issue of aggressive behaviour, primarily owing to a stronger awareness of children’s rights and parents’ responsibility to promote them. The number of systematic studies dealing with the relational level and the area of covert aggressive behaviour is limited. In the past, studies investigating aggressive behaviour primarily focused on its most typical manifestation, i.e. physical aggression. In the postmodern period, however, experts have begun to explore different forms of aggressive behaviour which are particularly typical of girls. In this study the authors focused on various forms of covert violence to which girls in elementary schools are exposed. The descriptions of behaviours provided by both teachers and girls reveal a variety of forms of covert aggression among girls as well as a range of related incidents and their causes.